2004
DOI: 10.1095/biolreprod.103.021709
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Differentially Expressed Genes in Granulosa Cells of Bovine Dominant Follicles Using Suppression Subtractive Hybridization1

Abstract: Development of antral follicles beyond 3 to 4 mm in cattle appears as a wave pattern that occurs two to three times during the estrous cycle. Each wave presents a cyclic recruitment of multiple follicles at the 3- to 4-mm stage, followed by the selection of a single follicle that becomes the dominant follicle (DF). The molecular determinants involved in the follicular dominance process remain poorly understood. The objective of the current study was to compare gene expression in granulosa cells (GCs) between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 81 publications
8
56
0
Order By: Relevance
“…Among them, three had already been selected by other experiments on cellular models: VIIC2 had been found in a differential hybridisation screening between control and FSH-treated pig granulosa cells (Tosser-Klopp et al, 1997), GPX and calpaïn had been found in suppression subtractive experiments between control and FSH-treated pig granulosa cells (Bonnet et al, 2006) and may play a role during folliculogenesis. NR5A2 transcript has been shown to be up-regulated in bovine dominant follicles, compared to small follicles (Fayad et al, 2004), which is consistent with our findings but has not been described yet in pig ovary. NPTX2 transcript regulation has never been described in granulosa cells.…”
Section: Discussionsupporting
confidence: 93%
“…Among them, three had already been selected by other experiments on cellular models: VIIC2 had been found in a differential hybridisation screening between control and FSH-treated pig granulosa cells (Tosser-Klopp et al, 1997), GPX and calpaïn had been found in suppression subtractive experiments between control and FSH-treated pig granulosa cells (Bonnet et al, 2006) and may play a role during folliculogenesis. NR5A2 transcript has been shown to be up-regulated in bovine dominant follicles, compared to small follicles (Fayad et al, 2004), which is consistent with our findings but has not been described yet in pig ovary. NPTX2 transcript regulation has never been described in granulosa cells.…”
Section: Discussionsupporting
confidence: 93%
“…These two transcripts encoded a novel 3 0 truncated aromatase variant (deposited under NCBI accession number DQ004742 and recently matched to Bt.4447), and an untranslated mRNA sequence recently matched to the UniGene cluster Bt.33875 (deposited under NCBI accession number AY999166). In addition, SAGE analysis of transcripts upregulated in the DF granulosa cells confirmed four known genes encoding cytochrome P450 aromatase (CYP19A1), glutathione S-transferase A2 (GSTA2), inhibin a-subunit (INHA) and glia-derived nexin (SERPINE2), which regulate follicular E synthesis, antioxidant activity and extracellular tissue remodelling in the selected DF (Mihm et al 1997, Sisco et al 2003, Evans et al 2004, Fayad et al 2004.…”
Section: Sage Analysis Of Differentially Expressed Transcripts In Thementioning
confidence: 92%
“…These proteins have diverse cellular functions in signalling (calreticulin (CALR)), metabolism (cytochrome c oxidase subunit VIIb (COX7B), glutathione peroxidase 1 (GPX1)), DNA binding (high-mobility group nucleosomal binding domain 2 (HMGN2), poly(rC) binding protein 1 (PCBP1)), RNA synthesis (non-POU domain containing, octamer binding (NONO)), protein synthesis (Tu translation elongation factor, mitochondrial (TUFM)) and metabolism (heat shock 70 kDa protein 8 (HSPA8), heat shock protein 90 kDa b (Grp94), member 1 (HSP90B1)) ( Table 2). The remaining three transcripts encoded genes (inhibin, b A (INHBA), hydroxy-d-5-steroid dehydrogenase, 3b-and steroid d-isomerase 1 (HSD3B1), tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein, 3 polypeptide (YWHAE)) previously found to show higher mRNA expression in the newly selected DF , Sisco et al 2003, Fayad et al 2004; Table 2). …”
Section: Sage Analysis Of Differentially Expressed Transcripts In Thementioning
confidence: 95%
See 1 more Smart Citation
“…Recent attempts to identify genes that regulate the selection and recruitment of follicles to develop into mature oocytes during the bovine estrous cycle by expression profiling led to the identification of ApoER2 as a candidate for such a function (10,11). In another study, ApoER2 has been shown to be preferentially expressed in bovine dominant follicles when compared with subordinate follicles (12).…”
mentioning
confidence: 99%